Implementasi algoritma random walk untuk menghasilkan procedural map pada game scrollbearer - Prayoga, Yosafat Rendi; Martyas Edi, Sri Winarso (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
The rapid growth of the gaming industry demands innovation in map design to maintain dynamic and non-repetitive gameplay experiences. This study aims to implement the Random Walk algorithm to generate procedural maps for Scrollbearer, a roguelike game developed using C# in Unity. The algorithm constructs random corridors and rooms from a starting point, integrated with dead end handling and Corridor First mechanics to ensure map connectivity. The research applies a Research and Development (R&D) approach with quantitative evaluation through Likert-scale questionnaires. Test results demonstrate that procedural maps significantly enhance replayability, with 79.5% of players preferring this mode due to unique layout variations and higher challenge levels (score 4.07/5). Exploration satisfaction in the procedural mode also outperformed the static mode (score 4.34/5). These findings validate the effectiveness of the Random Walk algorithm in creating dynamic maps for roguelike games, while providing a foundation for future enhancements such as biome diversity and random events.